Hubungan Tekanan Darah Dengan Mual Muntah Pasca Operasi Area Abdomen Dengan Anestesi Umum Di Ruang Pulih Sadar RS Lavalette Malang - Aulia, Anisa; Supono, Supono; Bachtiar , Arief; Marsaid (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: To discover the relationship between blood pressure and nausea vomiting after abdominal surgery with general anesthesia in the recovery room at Lavalette Hospital, Malang. Methods: The research design used a non-experimental quantitative descriptive method with a cross-sectional correlation approach. The sampling used purposive sampling with non-random sampling technique, totaling 33 respondents. Results: The research results showed that the average systolic blood pressure of respondents was 110, the average diastolic blood pressure of respondents was 81, and the majority of respondents experienced moderate nausea and vomiting. The results of the Spearman rank correlation test showed a p-value of 0.001 for the systolic blood pressure variable and a p-value of 0.002 for the diastolic blood pressure variable for postoperative nausea and vomiting. Conclusion: There is a significant relationship between blood pressure and nausea vomiting after abdominal surgery with general anesthesia in the recovery room at Lavalette Hospital, Malang. It is hoped that the hospital, especially nurses, will pay attention in nursing care to the importance of dealing with post-operative nausea and vomiting